Teacher Motivation for Quality Output - Patrick Kongnyuy (Current Research in Language, Literature and Education Vol. 2, 2021)
Motivation is very instrumental in personnel management. Empirical evidence points to the fact that motivation has been discovered to enhance teachers’ output. Teachers’ feelings, behaviour, attached value (worth) and the environment determines the amount of effort put in for the attainment of school objectives. Satisfied teachers are generally productive and can influence students’ achievement. This chapter elucidates the concept of motivation and elaborates models of motivation for teachers output. It also has as objective, to elaborate the factor of teachers’ motivation and their output, exploring how teachers can be motivated to perform better in their teaching tasks. It is concluded that, boasting teachers’ morale, promotion of teachers, good work environment and cordial interpersonal relationships positively influenced teachers’ output.